THE INFLUENCE OF WORK BALANCE, WORK DISCIPLINE, AND EMPLOYEE MOTIVATION ON EMPLOYEE PERFORMANCE OF AUTOMOTIVE CARS IN PALOPO CITY - Nurhayani, Nurhayani; Junaidi, Junaidi; Duriani, Duriani (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to investigate the effect of work balance, work discipline, and employee motivation on the performance of Palopo city car automotive employees. The method used in this research is a quantitative method. Data were analyzed using structural equation modeling (SEM), a multivariate analysis technique used to help understand complex relationships between observed and latent variables. Multivariate analysis is to analyze the influence of independent variables on dependent variables. This research was tested using SMARTPLS4. The sample used in this research is 50 employees, and the population is all employees of Palopo City Car Autos. The results of this study indicate that work-life balance has a positive and significant effect on employee motivation. Work discipline has a positive and significant effect on employee motivation. Work-life balance has a positive and significant effect on employee performance. Work discipline has a positive and significant effect on employee performance. Employee motivation has a positive and significant influence on employee performance. Keywords: Work Balance; Discipline; Employee Motivation; Employee Performance